The Impact of Land Mafia on Agrarian Disputes and the Optimisation of Electronic Land Transfer Deeds in Indonesia - Aslan Noor; Suci Rahmawati; Tara Devilia Hidayati; Rina Rosmiati; Muhammad Reifal adenafio; Ahmad Yusuf Nurwanda; Arief Satriawan (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
This study investigates the impact of land mafia practices on land conflicts and disputes in Indonesia and evaluates the potential of electronic land administration policies to enhance legal certainty. Land remains one of the nation’s most strategic resources, yet its governance has been undermined by systemic irregularities and organized criminal practices. Land mafia activities ranging from document forgery and duplicate certificates to collusion with state officials have generated prolonged disputes, eroded public trust in the legal system, and hindered investment in the property and infrastructure sectors. The research employs a normative legal method, focusing on statutory analysis and doctrinal review to identify principles, norms, and legal frameworks relevant to the problem. Primary legal sources include national agrarian legislation and Ministerial Regulation ATR/BPN No. 3 of 2023, while secondary and tertiary sources encompass scholarly literature, journal articles, and legal reference materials. This conceptual approach allows for a systematic evaluation of both the challenges posed by land mafia practices and the opportunities offered by digital transformation in land governance. The findings indicate that land mafia practices cause significant legal uncertainty, particularly through falsified and duplicate certificates, which create conflicting ownership claims and protracted litigation. Such conditions not only harm individual landholders but also weaken the national economy by discouraging investment. In response, the government’s introduction of electronic land certificates provides a promising reform, offering enhanced transparency, security, and efficiency in land administration. Nevertheless, challenges remain, including resistance from vested interests, cybersecurity risks, and unequal access to digital platforms. The study concludes that combating land mafia practices requires a comprehensive approach that integrates technological innovation with institutional strengthening, professional accountability, and community participation. The contribution of this research lies in highlighting the normative and policy dimensions of land governance reform, while also identifying critical areas for further interdisciplinary and empirical investigation. By addressing these issues, the study advances the discourse on sustainable, transparent, and equitable land governance in Indonesia.